Ants from Northwestern China (Hymenoptera, Fomficidae) - Cedric Collingwood; Harold Heatwole (Psyche: A Journal of Entomology)
An ecological survey of the ant fauna of the southern part of the Junggar Basin and adjacent mountains, Xinjiang, China, revealed 46 species of which 27 (59%) were new records for China. Most of the species are widespread and no endemics were found. A largely boreal fauna occupies the spruce forest zone at high elevations of the Tienshan Mountains, giving way, lower down, in elm forest, to a mixed, but primarily mesic temperate fauna. Loess desert and degraded steppe at mid-elevations and in the foothills are overgrazed and have only a few species that elsewhere occur in temperate mesic and/or steppic habitats. The sandy deserts and poplar woodlands of the arid Junggar Basin have a fauna characteristic of deserts and steppes. The salt desert fauna has a strange mixture of a number of elements.